2021
DOI: 10.1155/2021/5557184
|View full text |Cite
|
Sign up to set email alerts
|

A Sentence‐Level Joint Relation Classification Model Based on Reinforcement Learning

Abstract: Relation classification is an important semantic processing task in the field of natural language processing (NLP). Data sources generally adopt remote monitoring strategies to automatically generate large-scale training data, which inevitably causes label noise problems. At the same time, another challenge is that important information can appear at any place in the sentence. This paper presents a sentence-level joint relation classification model. The model has two modules: a reinforcement learning (RL) agen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“… JOINT_PCNN + RL . This work [ 26 ] introduced a RL framework to jointly train a sentence-level relation extraction model …”
Section: Resultsmentioning
confidence: 99%
“… JOINT_PCNN + RL . This work [ 26 ] introduced a RL framework to jointly train a sentence-level relation extraction model …”
Section: Resultsmentioning
confidence: 99%
“…Relation extraction is also an important NLP task. Liu et al ( 33 ) combined Bi-LSTM and an attention mechanism as a joint model to process the text features of sentences and classify the relation between two entities. The experimental results demonstrated that the model can effectively deal with data noise and achieve better relation classification performance at the sentence level.…”
Section: Discussionmentioning
confidence: 99%
“…Supplementary Table 2 and Supplementary Text 1 explain how NLPs and LLMs work. NLP algorithms can be combined with reinforcement learning [ 17 ] to train them to take actions to maximize a reward [ 18 ]. As seen with ChatGPT and GPT-4, in some instances, an NLP model is trained to generate responses to user inputs, and a reinforcement learning algorithm is used to adjust the model to maximize the likelihood of generating appropriate and coherent responses.…”
Section: How Do Chatbots Work?mentioning
confidence: 99%